Investigação do processo Fenton heterogêneo no tratamento de lixiviado de aterro sanitário - Quirino, Amanda Gondim Cabral (2021)
Leachates are highly complex effluents resulting from the combination of waste degradation and the water cycle in a landfill. The aim of this work was to investigate the heterogeneous Fenton process using the solid catalyst nickel-zinc ferrite (Ni0.5Zn0.5Fe2O4) in the treatment of leachate from the Metropolitan Sanitary Landfill of João Pessoa (ASMJP). For this, initially, a bibliometric and systematic study was conducted about the application of heterogeneous Fenton processes in the treatment of landfill leachate, considering the publication period of 2015-2020, according to the methodology ProKnow-C (Knowledge Development Process – Constructivist). The practical investigations were conducted according to a Central Composite Design (CCD) associated with the Response Surface Methodology (RSM). The input variables adopted were pH (2.98 to 8.02), catalyst concentration (0.66 to 2.34 g/L) and H2O2 factor (0.33 to 1.17), where [H2O2] = H2O2 factor x 2.125 x COD raw leachate, which corresponded to a variation of H2O2 from 6,311.25 to 22,376.25 mg/L (0.19 to 0.66 mol/L) for a COD of 9,000 mg/L of the raw leachate. The response variable to measure the treatment efficiency was the discoloration from the raw leachate. As a result, a mathematical model with an R2 of 0.9597 was generated and the RSM enabled the determination of the optimum point (pH: 8.02, catalyst concentration: 0.66 g/L, H2O2 factor: 1.1450) for discoloration, which corresponded to a efficiency of 89.7%. The model generated by the regression of the experimental data was experimentally validated in the optimized condition, in triplicate, and it showed a satisfactory fit between the theoretical response and those obtained experimentally. Furthermore, in the optimized condition, the leachate’s spectral response to heterogeneous Fenton and to isolated processes (only H2O2 or Ni0.5Zn0.5Fe2O4) were investigated, and it was found that the absorbances peaks removals of simple aromatic compounds (228, 254 and 284 nm) and conjugated (310 nm), as well as the reduction of the integrated spectral area from 200 to 800 nm obeyed the efficiency order: Ni0.5Zn0.5Fe2O4/H2O2 > H2O2 > Ni0.5Zn0,5Fe2O4, which elucidated the effectiveness of the heterogeneous Fenton process in discoloring landfill leachate and removing recalcitrant compounds present in the raw leachate.